Implementation of the Five-Star Paradigm in the Family and Community Medicine Residency Training Program The Philippine General Hospital experience - Mercado, Maria Teresa Rosario G.
Background of the Study: The residency training program in Family and Community Medicine (FCM) at the University of the Philippines Manila - Philippine General Hospital (UP-PGH) has been following the five-star paradigm since 1998. The curriculum aimed for the resident physician as: doctor, teacher, councelor, researcher and manager. Objectives: To compare the level of satisfaction of the RPTs of FCM in UP-PGH in performing the expected competencies in the different rotations according to the five-star model; and to determine the factors that influenced the achievement of the expected competencies. Methodology: This ia a descriptive study on the level of satisfaction of the RPTs of FCM in UP-PGH in terms of performing their expected competencies in the different roations. A modified checklist was administered. Focused group discussions (FGDs) were also done. Information gathered from FGDs was processed using content analysis. Results: The clinician role was generally achieved satisfactorily by the three year levels of the RPTs in their rotations; followed by the counselor, teacher, mamager and researcher roles. Conclusion: Rotations in the various clinical areas in the residency training program of FCM were perceived by the RPTs to be most contributory to the development of their professional competencies. In some clinical areas, the RPTs perceived themselves to be unwanted which reflects how the specialty is perceived by other clinical disciplines in Medicine. Recommendation: The RPTs would appreciate adequate orientation prior to each rotation; regular feedback sessions; regular mentoring; and use of learning portfolio.
Theses--(Master of Science in Clinical Medicine - Family Medicine) UPCM
Keywords: Training Programs; Medical education; Internship and Residency